2020
DOI: 10.1002/ppsc.201900487
|View full text |Cite
|
Sign up to set email alerts
|

Adsorber Particles with Magnetically‐Supported Improved Electrochemical Conversion Behavior for Waste Water Treatment Processes

Abstract: Micron‐sized supraparticles, consisting of a plurality of discrete nano‐ and microscale functional units, are assembled and fused by means of a droplet extrusion process. By combining nano magnetite, activated carbon, and conductive carbon with a polymeric binder matrix, particles are obtained which unite good magnetic properties, electrical conductivity, and adsorber activity through the high accessible surface area of the incorporated activated carbon of about 570 m2 g−1, thereby enabling a new approach towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…In consequence, all experiments of this section are conducted with an electrode particle mass of 3 g for the fluidized bed electrode. In previous investigations, it could also be shown that the superposition of the fluidized bed electrode by a magnetic field leads to an improvement of the electrochemical conversion by enhancing the conductivity of the fluidized bed electrode [10,13,14]. In this work we investigate the effect of the superposition of a magnetic field in the presence of nonconductive particle suspensions.…”
Section: Influence Of Solid-containing Reaction Solutionsmentioning
confidence: 95%
See 2 more Smart Citations
“…In consequence, all experiments of this section are conducted with an electrode particle mass of 3 g for the fluidized bed electrode. In previous investigations, it could also be shown that the superposition of the fluidized bed electrode by a magnetic field leads to an improvement of the electrochemical conversion by enhancing the conductivity of the fluidized bed electrode [10,13,14]. In this work we investigate the effect of the superposition of a magnetic field in the presence of nonconductive particle suspensions.…”
Section: Influence Of Solid-containing Reaction Solutionsmentioning
confidence: 95%
“…The specific resistance of a dry, gently compressed particle bed was approximately 0.5 Ωm. A detailed description of the particles and their synthesis can be found in [10,13,14]. For further characterization the magnetization curve of the electrode particles was determined (see Fig.…”
Section: Magnetic Electrode Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The surface topography and composition of supraparticles can be controlled via mixtures of different primary particle sizes and materials, creating hierarchical porous 27 materials with gradients 13 for catalysis 28 and tissue engineering 29 or powders with enhanced flowability for additive manufacturing. 30 Incorporating functional primary particles encodes additional properties into such supraparticles, such as magnetic actuation, 31 efficient separation, 32 object identification, 33 T h i s c o n t e n t i s antitampering, 34 lasing, 35 photothermal conversion, 36 and drug delivery. 37 Supraparticles also serve as model systems in soft condensed matter, providing insights for fundamental questions on structure formation, 6,7,38,39 crystallization pathways, 8,40 and the number−structure−property relationship 9,41 of confined finite systems.…”
Section: Introductionmentioning
confidence: 99%